Epstein-Barr Virus DNA Enhances Diptericin Expression and Increases Hemocyte Numbers in Drosophila melanogaster via the Immune Deficiency Pathway - Sherri, Nour; Salloum, Noor; Mouawad, Carine; Haidar-Ahmad, Nathaline; Shirinian, Margret; Rahal, Elias A. (Frontiers in Microbiology, 2018)
Infection with the Epstein-Barr virus (EBV) is associated with several malignancies and autoimmune diseases in humans. Following EBV infection and establishment of latency, recurrences frequently occur resulting in potential viral DNA shedding, which may then trigger the activation of immune pathways. We have previously demonstrated that levels of the pro-inflammatory cytokine IL-17, which is associated with several autoimmune diseases, are increased in response to EBV DNA injection in mice. Whether other pro-inflammatory pathways are induced in EBV DNA pathobiology remains to be investigated. The complexity of mammalian immune systems presents a challenge to studying differential activities of their intricate immune pathways in response to a particular immune stimulus. In this study, we used Drosophila melanogaster to identify innate humoral and cellular immune pathways that are activated in response to EBV DNA. Injection of wild type adult flies with EBV DNA induced the Immune Deficiency (IMD) pathway resulting in enhanced expression of the antimicrobial peptide diptericin. Furthermore, EBV DNA increased the number of hemocytes in flies. Conditional silencing of the IMD pathway decreased diptericin expression in addition to curbing of hemocyte proliferation in response to challenge with EBV DNA. Comparatively, upon injecting mice with EBV DNA, we detected enhanced expression of Tumor Necrosis Factor-α (TNFα); this enhancement is rather comparable to IMD pathway activation in flies. This study hence indicates that Drosophila melanogaster could possibly be utilized to identify immune mediators that may also play a role in the response to EBV DNA in higher systems.